Bridging the Great Divide—A Response to Linda Greenhouse and Reva B. Siegel's Before (and After) Roe v. Wade: New Questions About Backlash - Lolita Buckner Inniss (Washington University Law Review, 2012)
This essay discusses the history of Roe v. Wade as recently addressed by Linda Greenhouse and Reva B. Siegel. Going beyond their assertions, I suggest that an additional, more encompassing inquiry focuses on what factors are implicated in the politics of abortion and how these factors relate to larger social, political, and cultural conflicts both before and after Roe. By naming party politics and the Catholic Church, Greenhouse and Siegel posit two crucial elements that shaped the abortion debate. I assert, however, that what is not discussed in their Article is the way numerous other factors have figured into the debate, race and class being two of the most salient. Race, class, and abortion have interacted in complex and numerous ways throughout United States history. While this interaction in some respects can be described via a linear, historical approach, it is not fully explicated by a single dichotomous before/after analysis centered on Roe. Instead, race, class, and abortion are constantly interacting, sometimes co-constructed, constituent parts of a much greater social, cultural, and political conversation in the United States. I suggest that if national party politics and the Catholic Church are important aspects of the development of the United States narrative on abortion, then race and class are telling and even compelling subtexts in that narrative. Giving attention to these subtextual strands may offer valuable additional insights.
Keywords: Roe v. Wade 410 U.S. 113 (1973); Abortion; Sexual liberation; United States; Greenhouse; Linda